Sophie's World: An Educational Experience on the implementation of the Course of Philosophy for Schools in Peru (FPN) - Esteban Chocce, José (2019)
Our country has many problems to solve in order to attain its development, and due to the lack of conscious education policies on proper interpretation of our reality. This means that in the popular imagination still reigns beliefs, myths and prejudices that prevent us from having a clear and distinct on their social, economic, political, etc., where the Peruvian population is involved. A signal and displays it, is their lack of knowledge of philosophical thought. Peruvian Education today has many problems, for example, is to restore the course of philosophy in high school. This paper aims at raising awareness of the Pilot Course of Philosophy for Children (FPN) in private schools in Lima (Engineering Consortium). Which was inspired by the Project of Philosophy Matthew Lipman in the U.S. and Carmen Zavala in Peru (Peruvian Society for Philosophical Practice and Philosophical Counseling "SOPECPRAFIL") who began with the first pilot projects of Philosophy in Lima. Therefore, our project aims to contribute to our little experience in the IEP "Engineering." The teaching of philosophy in primary and secondary education is very successful and well received globally but in Peru there was well received thanks to the apathy and the political and social context that crossed (Carmen Zavala's Experience). Accordingly, giving us manifest our educational experience seeks to promote a debate on the scientific community in general on the implementation of philosophy in education in Peru. The purpose of the course Philosophy is alienate the learner with the exercise of our reasoning, giving new conceptual tools for argumentation, educate our spirit of democratic tolerance, ethical practice and research and questioning about their own reality.